Data from NCI Cancer Research Data Commons: Cloud-Based Analytic Resources - David Pot; Zelia Worman; Alexander Baumann; Shirish Pathak; Rowan Beck; Erin Beck; Katherine Thayer; Tanja M. Davidsen; Erika Kim; Brandi Davis-Dusenbery; John Otridge; Todd Pihl; et al. (2024)
AbstractThe NCI's Cloud Resources (CR) are the analytical components of the Cancer Research Data Commons (CRDC) ecosystem. This review describes how the three CRs (Broad Institute FireCloud, Institute for Systems Biology Cancer Gateway in the Cloud, and Seven Bridges Cancer Genomics Cloud) provide access and availability to large, cloud-hosted, multimodal cancer datasets, as well as offer tools and workspaces for performing data analysis where the data resides, without download or storage. In addition, users can upload their own data and tools into their workspaces, allowing researchers to create custom analysis workflows and integrate CRDC-hosted data with their own.See related articles by Brady et al., p. 1384, Wang et al., p. 1388, and Kim et al., p. 1404